The Description of Work Stress Among Medical Record Officers in the Coding Section at Haji General Hospital Medan in 2024 - Faadyah, Siti; Ritonga, Zulham Andi; Karo Karo, Siddik; Hulu, Delisman (CV. Devitara, 2025)
Stress is the result of an imbalance between demands and the resources an individual possesses—the greater the gap, the higher the level of stress experienced, which can pose a threat to well-being. The aim of this study was to describe the work stress experienced by medical record officers in the coding section at Haji General Hospital Medan in 2024. This study employed a qualitative research method. The informants included four individuals: one outpatient coding officer, two inpatient coding officers, and one head of the medical record installation. The findings revealed that the causes of work stress among coding officers included workload, work-related conflicts, inadequate work equipment, and poor working environment. It is recommended that the hospital provide adequate workspace and facilities that ensure comfort for the officers. Additionally, coding officers should pay more attention to task distribution and provide education to other healthcare workers to ensure timely delivery of medical record files for coding. Officers must also maintain effective communication with other healthcare personnel to prevent conflicts and misunderstandings.